Knowledge of Sleep Medicine Among Practicing Doctors in A Nigerian Community (Western Journal of Medical and Biomedical Sciences, 2024)
Sleep disorders are common medical condition globally including Nigeria. It affects all categories of persons and age groups thereby posing a great burden on the sufferers. Despite this, there is dearth of studies focusing on this specialty as well as low knowledge and under-recognition of sleep disorders among practicing medical professionals. This study was designed to assess the awareness and knowledge of sleep medicine among practicing clinicians in Nigeria. It was cross-sectional hospital-based descriptive study using a convenient sampling method. The knowledge of sleep medicine among practicing doctors in three Nigerian hospitals was assessed with Assessment of Sleep Knowledge in Medical Education (ASKME) instrument. Data was analyzed using SPSS version 21. There were 149 participants that were interviewed. The majority, 94 (63.1%) were males and 55 (36.9%) were females. Professional designations of the participants were: 67 (45.0%) House officers, 32 (21.5%) Medical officers, 35 (23.5%) Resident doctors and 15 (10.1%) were Consultants (Specialist). Most physicians, 96 (64.4%) had low level of knowledge while 53 (35.6%) had high level of knowledge. There was no correlation between level of knowledge and years of medical practice. Most respondents 69 (46.3%) advocated the introduction of sleep medicine in undergraduate medical curriculum. Knowledge and awareness of sleep medicine among practicing clinicians is low and does not correlate with the number of years of practice. There is the need to integrate sleep medicine into medical training and in continuous medical education and to promote specialization in the field in Nigeria.
Keywords: Awareness, Knowledge; Medical Training; Nigeria, Sleep Disorders; Sleep Medicine